The truth about knowing how to negotiate : the essential truths in 20 inutes - Thompson, Leigh L. (Truth about (FT Press), 2007)
"The 53 Truths provide incredible insight into the art and science of negotiating. This is a must read for sales professionals but is equally beneficial to all who wish to be better negotiators."--CHRIS WEBER, Vice President, West Region Enterprise, Microsoft Corporation "Negotiation skills can and must be learned. In her new book, Leigh provides the framework. A must read for negotiators at all levels of ability." -ANTHONY SANTIAGO, Vice President, Global Sourcing & Supplier Management, Bristol-Myers Squibb "A superbly presented summary of practical tools and techniques for negotiating in all types of situations, and creating win-win solutions that result in enduring business relationships. Provides substantiated evidence of what works successfully-and pitfalls to avoid-in the game of negotiation." -RUSSELL D'SOUZA, International Credit Manager, Hallmark Cards, Inc. You can learn to be a world-class negotiator and get what you want! " The truth about how to prepare within one hour " The truth about negotiating with friends, colleagues, and spouses " The truth about the win-win litmus test This book reveals 53 PROVEN NEGOTIATION PRINCIPLES and bite-size, easy-to-use techniques that work